Thomas Oliver Selfridge papers - Selfridge, Thomas Oliver, 1804-1902.
Correspondence, journals, logbooks, notebooks, and other papers relating to Selfridge's naval career. Includes material relating to his service as commander of the USS Mississippi and of the Mare Island Naval Shipyard, Calif., and as president of the U.S. Naval Examining Board (Line). Correspondents include his son, T.O. Selfridge, Henry E. Ballard, George E. Belknap, A.F. Crossman, Francis E. Grice, and David D. Porter.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Ballard, Henry E. -- Correspondence; Belknap, George E. -- 1832-1903 -- Correspondence; Crossman, A. F., -- -1872 -- Correspondence; Grice, Francis E., -- 1829- -- Correspondence; Porter, David D. -- 1813-1891 -- Correspondence; Selfridge, T. O. -- 1836-1924 -- Correspondence; United States. -- Naval Examining Board (Line); United States. -- Navy -- Officers; Mare Island Naval Shipyard; Mississippi (Side-wheel steamer); Navy-yards and naval stations -- California; Naval officers